Alkali-free, fluorine-free, and chlorine-free high-efficiency quick-setting agent and preparation method thereof

By using aluminum sulfate and other ingredients such as aluminum sulfate and other ingredients, it has solved the problem of the existing speed condensate to the human body and machinery, and the early insufficient concrete intensity of the concrete, and achieved efficient concrete solidification and intensity improvement.

CN119143417BActive Publication Date: 2025-01-28SHANDONG QISHENG NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411644416.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-28
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Existing fast-setting agents containing alkali, fluorine, and chlorine are harmful to human bodies and machinery, and the early strength of concrete after use is insufficient, making it difficult to meet national standards, which can easily lead to concrete collapse and landslides in tunnels.

Method used

Polyte sulfate is used as the main component, with homemade multi -polyetric thickening agent, hardening promoter and modified nano -nanocrilis silica, forming an efficient fluorine -free and non -chlorine -free -without chlorine -free speed condenser. This speed condenser reduces the rebound of jet concrete through a multi -polymerized thickener, and the hardening promoter accelerates the hydration process, thereby shortening the coagulation time and increasing the intensity.

Benefits of technology

The high -efficiency speed coagulant of the alkali -free, non -chlorine, non -chlorine -free, non -efficient chlorine, and the final condensation time is short. After use, the concrete has a high pressure resistance and reservation rate, which reduces the harm to the human body and machinery. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143417B_ABST
    Figure CN119143417B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of building materials, and specifically relates to an alkali-free, fluorine-free, and chlorine-free high-efficiency quick-setting agent and a preparation method thereof. The quick-setting agent of the present invention is mainly composed of polyaluminum sulfate, aluminum triformate, ethylene glycol ethyl ether, polymer thickener, modified nano silicon dioxide, hardening accelerator, calcium formate, and water, wherein the polymer thickener is better than the conventional thickener, can minimize the rebound of the shotcrete during the actual application process, the hardening accelerator can accelerate the hydration process, thereby shortening the setting time and improving the strength, etc., and the modified nano silicon dioxide can stabilize the various components of the quick-setting agent. The alkali-free, fluorine-free, and chlorine-free high-efficiency quick-setting agent prepared by the present invention has performance that meets the relevant standards after testing, the finished product is less harmful to the human body, the initial setting and final setting times are short, and the concrete has a higher compressive strength and retention rate after use, and has excellent performance, and can be efficiently applied to the construction industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and particularly relates to an alkali-free, fluorine-free, and chlorine-free high-efficiency quick-setting agent and a preparation method thereof. Background Art

[0002] Accelerators refer to admixtures added to concrete that can cause shotcrete to set and harden quickly. Accelerators can be divided into powder and liquid according to product form (according to the dispersion state of solid matter in it, they can be divided into solution type and suspension type). Accelerators can be divided into alkali-containing and alkali-free according to alkali content. Alkali-containing accelerators refer to accelerators with a sodium oxide equivalent content greater than 1.0% and less than the control value of the manufacturer, and alkali-free accelerators refer to accelerators with a sodium oxide equivalent content of no more than 1.0%.

[0003] Alkali, fluorine and chlorine-containing quick-setting agents have the following problems: they are harmful to the human body. In the absence of protective measures, they can cause the human skeleton to soften, and in severe cases, they can cause irreversible disability. Inhalation of hydrofluoric acid mist can cause bronchitis and pulmonary edema. Hydrofluoric acid can also be absorbed through the skin and cause serious poisoning. They are harmful to machinery and have a strong corrosive effect. In a short period of time, they will cause serious corrosion to the equipment (pumping system) and delivery pipelines and nozzles using the quick-setting agent. They have an impact on construction. It is difficult for the 24-hour strength to meet the national standard. During the excavation work on the second day, the concrete collapses and the tunnel collapses easily due to insufficient strength and vibration from blasting operations. Other hidden hazards include water seepage in the concrete or chemical reactions in a humid environment, which will reduce the strength of the concrete and cause irreparable losses.

[0004] Early accelerators were mainly composed of alkali metal aluminum salts and aluminates, which had excellent quick-setting effects. However, due to the high alkali content, they were prone to alkali-aggregate reactions with active aggregates in concrete, which would cause internal expansion of concrete and reduce the durability of concrete. Therefore, accelerators gradually developed in the direction of low alkali and alkali-free. Chloride ions contained in accelerators will have a serious corrosive effect on the steel bars and other metal embedded parts in the concrete. Specifically, chloride ions will penetrate the passivation film on the surface of the steel bars, thereby accelerating the corrosion of the steel bars. Excessive fluoride ions contained in accelerators will reduce the early strength of shotcrete and also have certain harm to the health of construction workers. As a result, alkali-free, chlorine-free, and fluorine-free accelerators have received more and more attention, but there are many differences in the early strength, later strength, and quick-setting effect of such products after application, and further development is needed. Summary of the invention

[0005] Based on the above problems, the present invention provides an alkali-free, fluorine-free, and chlorine-free high-efficiency quick-setting agent, which uses polyaluminium sulfate as the main component, and is matched with a self-made polymeric thickener and a hardening accelerator, etc., wherein the polymeric thickener is better than the conventional thickener, and can minimize the rebound of the shotcrete during the actual application process, and the hardening accelerator can accelerate the hydration process, thereby shortening the setting time and improving the strength, etc., and the modified nano-silica can stabilize the various components of the quick-setting agent. The alkali-free, fluorine-free, and chlorine-free high-efficiency quick-setting agent prepared by the present invention has performance that meets the relevant standards after testing, the finished product has less harm to the human body, the initial setting and final setting times are short, and the concrete has a higher compressive strength and retention rate after use, and has excellent performance.

[0006] The invention provides an alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent, the components of which are as follows by mass: 40-50 parts of polyaluminium sulfate, 3-8 parts of aluminium triformate, 1-1.5 parts of ethylene glycol ethyl ether, 2-3 parts of polymer thickener, 1-3 parts of modified nano-silicon dioxide, 3-5 parts of hardening accelerator, 1-2 parts of calcium formate and 50-60 parts of water;

[0007] Further, the mass parts of polyaluminium sulfate are 45-48 parts;

[0008] Furthermore, the mass fraction of aluminum triformate is 4-6 parts.

[0009] The preparation method of the polymeric thickener is as follows:

[0010] V1. Acrylic acid and N,N-dimethylacrylamide are weighed in a molar ratio of 1-3:1 to obtain a mixture 1, and mixture 1 and water are weighed in a volume ratio of 1:10-15, and the pH is adjusted to 7.0 to obtain a mixture 2, nitrogen is introduced into the mixture 2, and an ammonium persulfate solution is added dropwise, and the mixture is heated and stirred continuously for 4-5 hours, and cooled to room temperature to obtain a mixture 3;

[0011] V2. The mixture 3 obtained in step V1 is centrifuged at 4000-5000g, the supernatant is discarded, the precipitate is washed 3-5 times with deionized water, and the precipitate after centrifugation again is dried to obtain a polymeric thickener.

[0012] Preferably, in step V1, sodium hydroxide is used to adjust the pH, the amount of nitrogen introduced is preferably 8-10 L / min, the mass percentage concentration of the ammonium persulfate solution is 1-3%, the amount of the ammonium persulfate solution added is 5-8% of the volume of the mixture 2, the heating temperature is preferably 60-70° C., and the stirring speed is preferably 80-120 rpm.

[0013] The preparation method of the modified nano silicon dioxide is as follows:

[0014] L1. Stearic acid and anhydrous ethanol were mixed in a mass volume ratio of 1 g: 5-7 mL, heated to 45-55° C., and stirred at a speed of 500-600 rpm until uniformly dispersed to obtain solution 1;

[0015] L2. Add the nano-silica particles to the solution 1 obtained in step L1, disperse them by ultrasonic treatment, heat them to 55-65°C and maintain them for 2-3 hours, filter them, wash them with anhydrous ethanol, and dry them to obtain modified nano-silica.

[0016] Preferably, in step L2, the nano-silicon dioxide particles preferably have a particle size of 20-100 nm and a purity of more than 99%, and the ultrasound is preferably performed at a power of 150-200w.

[0017] The preparation method of the hardening accelerator is as follows:

[0018] S1. Aluminum nitrate and lithium nitrate are added to water and stirred until uniformly dispersed to obtain solution 2, sodium hydroxide and sodium carbonate are added to water and stirred until uniformly dispersed or solution 3 is obtained;

[0019] S2. Add solution 2 and solution 3 obtained in step S1 dropwise and grind to mix. After completion, let stand at 80-90°C for 1-3h, centrifuge to obtain a precipitate, wash the precipitate with deionized water for 3-5 times, add dopamine hydrochloride solution, stir at 280-320rpm at room temperature for 2-3h, centrifuge after completion, and dry the precipitate to obtain a hardening accelerator.

[0020] Preferably, in step S1, the molar ratio of aluminum nitrate: lithium nitrate is 1:1, the concentration of aluminum nitrate in solution 2 is 1.2-1.5 mol / L, the molar ratio of sodium hydroxide: sodium carbonate is 1.2:1, and the concentration of sodium hydroxide in solution 3 is 0.9-1.2 mol / L;

[0021] Preferably, in step S2, grinding is preferably performed in a colloid mill with a rotor speed of 3500-4000 rpm for 3-5 min, the mass percentage concentration of the dopamine hydrochloride solution is 0.5-0.8%, and the mass volume ratio of precipitate: dopamine hydrochloride solution is 1 g: 10-15 mL.

[0022] The present invention also provides a method for preparing an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent, and the specific steps are as follows:

[0023] M1. Weigh the components in parts by mass, dissolve the polyaluminum sulfate in 10-20 parts of water, then add the hardening accelerator and ethylene glycol ether, heat to 70-80 ° C and stir until uniformly dispersed to obtain a solution 4;

[0024] M2. Dissolve aluminum triformate, calcium formate and modified nano-silica in the remaining mass parts of water and stir until uniformly dispersed to obtain a solution 5;

[0025] M3. The solution 4 obtained in step M1 is mixed with the solution 5 obtained in step M2, and the polymer thickener is slowly added, and stirred until it is evenly dispersed to obtain an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent.

[0026] The beneficial effects of the present invention are as follows:

[0027] Alkali-free quick-setting agent is usually obtained by combining aluminum sulfate as the main component with other components such as thickener, alcohol amine, organic acid or inorganic acid after reasonable configuration. On this basis, the present invention adopts polyaluminum sulfate as the main component. The advantage of polyaluminum sulfate is that it has a higher Al2O3 content and lower cost, which can reduce the production cost of the quick-setting agent. In addition, the present invention adopts aluminum triformate, ethylene glycol ethyl ether, and calcium formate as auxiliary agents. The whole system of the quick-setting agent finally obtained is relatively stable, with a pH of about 3.0, which can effectively inhibit the hydrolysis and aggregation of aluminum sulfate. The polymer thickener prepared by the present invention replaces the thickener (such as polyacrylamide) used in conventional accelerator products. The polymer thickener can enhance the viscosity of shotcrete and reduce the rebound of shotcrete during actual application, which can not only avoid material waste but also provide certain protection for construction personnel. The modified nano-silica prepared by the present invention specifically adopts stearic acid to modify nano-silica particles. After the modified nano-silica is added to the accelerator, it can promote the hydration of silicate cement and stabilize the various components of the accelerator. The hardening accelerator prepared by the present invention is modified by dopamine hydrochloride on the basis of the advantages of layered double hydroxide. After the modification, the various properties of the accelerator can be improved after actual application, especially the solidification and strength performance of silicate cement.

[0028] The alkali-free, fluorine-free and chlorine-free high-efficiency quick-setting agent prepared by the present invention has performance that meets relevant standards after being tested, the finished product has less harm to human body, the initial setting and final setting times are shorter, and the concrete after use has higher compressive strength and retention rate, and can be efficiently applied to the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0030] Figure 1 This is a SEM picture of the accelerated setting agent obtained in Example 3 after being mixed with cement at a dosage of 7% and hydrated. DETAILED DESCRIPTION

[0031] In order to more clearly explain the overall concept of the present application, the following is described in detail in conjunction with the accompanying drawings of the specification by way of embodiment. In the following description, a large number of specific details are provided to provide a more thorough understanding of the present invention. However, it is obvious to those skilled in the art that the present invention can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present invention, some technical features well known in the art are not described.

[0032] Example 1: This example provides an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent, the components of which are as follows by mass: 40 parts of polyaluminum sulfate (purchased from Shanghai Yingxin Laboratory Equipment Co., Ltd.), 3 parts of aluminum triformate, 1 part of ethylene glycol ethyl ether, 2 parts of polymer thickener, 1 part of modified nano-silicon dioxide, 3 parts of hardening accelerator, 1 part of calcium formate and 50 parts of water;

[0033] The preparation method of the polymeric thickener is as follows:

[0034] V1. Acrylic acid and N,N-dimethylacrylamide were weighed in a molar ratio of 1:1 to obtain a mixture 1, and the mixture 1 and water were weighed in a volume ratio of 1:10, and the pH was adjusted to 7.0 with sodium hydroxide to obtain a mixture 2, nitrogen was introduced into the mixture 2 at a flow rate of 8 L / min, and a 1% ammonium persulfate solution with a mass percentage concentration of 5% of the volume of the mixture 2 was dripped, and the mixture was heated to 60°C and stirred at a speed of 80 rpm for 4 hours, and cooled to room temperature to obtain a mixture 3;

[0035] V2. The mixture 3 obtained in step V1 was centrifuged at 4000 g centrifugal force, the supernatant was discarded, the precipitate was washed three times with deionized water, and the precipitate was centrifuged again and dried to obtain a polymer thickener;

[0036] The preparation method of modified nano silicon dioxide is as follows:

[0037] L1. Stearic acid and anhydrous ethanol were mixed in a mass volume ratio of 1 g: 5 mL, heated to 45°C, and stirred at a speed of 500 rpm until uniformly dispersed to obtain solution 1;

[0038] L2. The nano-silica particles were added to the solution 1 obtained in step L1, and then dispersed by ultrasonic treatment at 150w power, heated to 55°C and maintained for 2h, and then filtered, washed with anhydrous ethanol, and dried to obtain modified nano-silica;

[0039] The preparation method of the hardening accelerator is as follows:

[0040] S1. Weigh 1.2 mol of aluminum nitrate and 1.2 mol of lithium nitrate, add them to 1 L of water, stir until evenly dispersed to obtain solution 2, weigh 0.9 mol of sodium hydroxide and 0.75 mol of sodium carbonate, add them to 1 L of water, stir until evenly dispersed to obtain solution 3;

[0041] S2. Add solution 2 and solution 3 obtained in step S1 dropwise, and mix them in a colloid mill at a rotor speed of 3500 rpm for 3 min. After the mixture is finished, the mixture is allowed to stand at 80° C. for 1 h, and centrifuged at a centrifugal force of 3000 g for 20 min to obtain a precipitate. The precipitate is washed 3 times with deionized water, and a dopamine hydrochloride solution having a mass percentage concentration of 0.5% is added. The mass volume ratio of the precipitate: the dopamine hydrochloride solution is 1 g: 10 mL. The mixture is stirred at a speed of 280 rpm at room temperature for 2 h. After the mixture is finished, the mixture is centrifuged. The precipitate is dried to obtain a hardening accelerator.

[0042] This embodiment also provides a method for preparing the alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent, and the specific steps are as follows:

[0043] M1. Weigh the components according to mass percentage, dissolve the polyaluminum sulfate in 10 parts of water, then add the hardening accelerator and ethylene glycol ethyl ether, heat to 70 ° C and stir until uniformly dispersed to obtain a solution 4;

[0044] M2. Dissolve aluminum triformate, calcium formate and modified nano-silica in the remaining 40 parts of water and stir until uniformly dispersed to obtain a solution 5;

[0045] M3. The solution 4 obtained in step M1 is mixed with the solution 5 obtained in step M2, and the polymer thickener is slowly added, and stirred until it is evenly dispersed to obtain an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent.

[0046] Example 2: This example provides an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent, the components of which are as follows by mass: 45 parts of polyaluminium sulfate (from the same source as in Example 1), 4 parts of aluminium triformate, 1.1 parts of ethylene glycol ethyl ether, 2.1 parts of polymer thickener, 1.4 parts of modified nano-silicon dioxide, 3.2 parts of hardening accelerator, 1.2 parts of calcium formate and 52 parts of water;

[0047] The preparation method of the polymeric thickener is as follows:

[0048] V1. Acrylic acid and N,N-dimethylacrylamide were weighed in a molar ratio of 2:1 to obtain a mixture 1, and the mixture 1 and water were weighed in a volume ratio of 1:12, and the pH was adjusted to 7.0 with sodium hydroxide to obtain a mixture 2, nitrogen was introduced into the mixture 2 at a flow rate of 8.4 L / min, and a 1.5% ammonium persulfate solution of 6% by volume of the mixture 2 was dripped, and the mixture was heated to 65° C. and stirred at a speed of 90 rpm for 4.2 h, and cooled to room temperature to obtain a mixture 3;

[0049] V2. The mixture 3 obtained in step V1 was centrifuged at 4100 g centrifugal force, the supernatant was discarded, the precipitate was washed three times with deionized water, and the precipitate was centrifuged again and dried to obtain a polymer thickener;

[0050] The preparation method of modified nano silicon dioxide is as follows:

[0051] L1. Stearic acid and anhydrous ethanol were mixed in a mass volume ratio of 1 g: 5.5 mL, heated to 48°C, and stirred at a speed of 540 rpm until uniformly dispersed to obtain solution 1;

[0052] L2. The nano-silica particles were added to the solution 1 obtained in step L1, dispersed by ultrasonic treatment at 180w power, heated to 58°C and maintained for 2.2h, filtered, washed with anhydrous ethanol, and dried to obtain modified nano-silica;

[0053] The preparation method of the hardening accelerator is as follows:

[0054] S1. Weigh 1.3 mol of aluminum nitrate and 1.3 mol of lithium nitrate, add them to 1 L of water, stir until evenly dispersed to obtain solution 2, weigh 1.0 mol of sodium hydroxide and 0.83 mol of sodium carbonate, add them to 1 L of water, stir until evenly dispersed to obtain solution 3;

[0055] S2. Add solution 2 and solution 3 obtained in step S1 dropwise, and mix them in a colloid mill at a rotor speed of 3600 rpm for 4 min. After the mixture is finished, the mixture is allowed to stand at 82° C. for 1.5 h, and centrifuged at a centrifugal force of 3200 g for 18 min to obtain a precipitate. The precipitate is washed three times with deionized water, and a dopamine hydrochloride solution having a mass percentage concentration of 0.6% is added. The mass volume ratio of the precipitate: the dopamine hydrochloride solution is 1 g: 12 mL. The mixture is stirred at a speed of 300 rpm at room temperature for 2.5 h. After the mixture is finished, the mixture is centrifuged. The precipitate is dried to obtain a hardening accelerator.

[0056] This embodiment also provides a method for preparing the alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent, and the specific steps are as follows:

[0057] M1. Weigh the components according to mass percentage, dissolve the polyaluminum sulfate in 12 parts of water, then add the hardening accelerator and ethylene glycol ethyl ether, heat to 72 ° C and stir until uniformly dispersed to obtain a solution 4;

[0058] M2. Dissolve aluminum triformate, calcium formate and modified nano-silica in the remaining 40 parts of water and stir until uniformly dispersed to obtain a solution 5;

[0059] M3. The solution 4 obtained in step M1 is mixed with the solution 5 obtained in step M2, and the polymer thickener is slowly added, and stirred until it is evenly dispersed to obtain an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent.

[0060] Embodiment 3: This embodiment provides an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent, the components of which are as follows by mass: 46 parts of polyaluminium sulfate, 5 parts of aluminium triformate, 1.2 parts of ethylene glycol ethyl ether, 2.4 parts of polymer thickener, 2 parts of modified nano-silicon dioxide, 3.8 parts of hardening accelerator, 1.5 parts of calcium formate and 55 parts of water;

[0061] The preparation method of the polymeric thickener is as follows:

[0062] V1. Acrylic acid and N,N-dimethylacrylamide were weighed in a molar ratio of 2.2:1 to obtain a mixture 1, and the mixture 1 and water were weighed in a volume ratio of 1:14, and the pH was adjusted to 7.0 with sodium hydroxide to obtain a mixture 2, nitrogen was introduced into the mixture 2 at a flow rate of 9 L / min, and a 2% ammonium persulfate solution with a mass percentage of 7% of the volume of the mixture 2 was dripped, and the mixture was heated to 66° C. and stirred at a speed of 100 rpm for 4.5 h, and cooled to room temperature to obtain a mixture 3;

[0063] V2. The mixture 3 obtained in step V1 was centrifuged at 4500 g centrifugal force, the supernatant was discarded, the precipitate was washed 4 times with deionized water, and the precipitate was centrifuged again and dried to obtain a polymer thickener;

[0064] The preparation method of modified nano silicon dioxide is as follows:

[0065] L1. Stearic acid and anhydrous ethanol were mixed in a mass volume ratio of 1 g: 6 mL, heated to 50°C, and stirred at a speed of 560 rpm until uniformly dispersed to obtain solution 1;

[0066] L2. The nano-silica particles were added to the solution 1 obtained in step L1, dispersed by ultrasonic treatment at 190w power, heated to 60°C and maintained for 2.5h, filtered, washed with anhydrous ethanol, and dried to obtain modified nano-silica;

[0067] The preparation method of the hardening accelerator is as follows:

[0068] S1. Weigh 1.4 mol of aluminum nitrate and 1.4 mol of lithium nitrate, add them to 1 L of water, stir until evenly dispersed to obtain solution 2, weigh 1.2 mol of sodium hydroxide and 1.0 mol of sodium carbonate, add them to 1 L of water, stir until evenly dispersed to obtain solution 3;

[0069] S2. Add solution 2 and solution 3 obtained in step S1 dropwise, and mix them in a colloid mill at a rotor speed of 3800 rpm for 4.5 min. After the mixture is finished, the mixture is allowed to stand at 85° C. for 2 h, and centrifuged at a centrifugal force of 3300 g for 16 min to obtain a precipitate. The precipitate is washed 4 times with deionized water, and a dopamine hydrochloride solution having a mass percentage concentration of 0.6% is added. The mass volume ratio of the precipitate: the dopamine hydrochloride solution is 1 g: 14 mL. The mixture is stirred at a speed of 310 rpm at room temperature for 2.8 h. After the mixture is finished, the mixture is centrifuged. The precipitate is dried to obtain a hardening accelerator.

[0070] This embodiment also provides a method for preparing the alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent, and the specific steps are as follows:

[0071] M1. Weigh the components according to mass percentage, dissolve the polyaluminum sulfate in 15 parts of water, then add the hardening accelerator and ethylene glycol ethyl ether, heat to 75 ° C and stir until uniformly dispersed to obtain a solution 4;

[0072] M2. Dissolve aluminum triformate, calcium formate and modified nano-silica in the remaining 40 parts of water and stir until uniformly dispersed to obtain a solution 5;

[0073] M3. The solution 4 obtained in step M1 is mixed with the solution 5 obtained in step M2, and the polymer thickener is slowly added, and stirred until it is evenly dispersed to obtain an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent.

[0074] Embodiment 4: This embodiment provides an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent, the components of which are as follows by mass: 48 parts of polyaluminium sulfate, 6 parts of aluminium triformate, 1.4 parts of ethylene glycol ethyl ether, 2.8 parts of polymer thickener, 2.4 parts of modified nano-silicon dioxide, 4.2 parts of hardening accelerator, 1.8 parts of calcium formate and 58 parts of water;

[0075] The preparation method of the polymeric thickener is as follows:

[0076] V1. Acrylic acid and N,N-dimethylacrylamide were weighed in a molar ratio of 2.5:1 to obtain a mixture 1, and the mixture 1 and water were weighed in a volume ratio of 1:15, and the pH was adjusted to 7.0 with sodium hydroxide to obtain a mixture 2, nitrogen was introduced into the mixture 2 at a flow rate of 9.5 L / min, and a 2.4% ammonium persulfate solution of 7.5% by mass percentage of the volume of the mixture 2 was dripped, and the mixture was heated to 68° C. and stirred at a speed of 110 rpm for 4.8 h, and cooled to room temperature to obtain a mixture 3;

[0077] V2. The mixture 3 obtained in step V1 was centrifuged at 4800 g centrifugal force, the supernatant was discarded, the precipitate was washed 5 times with deionized water, and the precipitate was centrifuged again and dried to obtain a polymer thickener;

[0078] The preparation method of modified nano silicon dioxide is as follows:

[0079] L1. Stearic acid and anhydrous ethanol were mixed in a mass volume ratio of 1 g: 6.5 mL, heated to 52°C, and stirred at a speed of 580 rpm until uniformly dispersed to obtain solution 1;

[0080] L2. The nano-silica particles were added to the solution 1 obtained in step L1, and then dispersed by ultrasonic treatment at 195w power, heated to 62°C and maintained for 2.8h. After the end, the modified nano-silica was obtained by filtering, washing with anhydrous ethanol, and drying;

[0081] The preparation method of the hardening accelerator is as follows:

[0082] S1. Weigh 1.5 mol of aluminum nitrate and 1.5 mol of lithium nitrate, add them to 1 L of water, stir until evenly dispersed to obtain solution 2, weigh 1.2 mol of sodium hydroxide and 1.0 mol of sodium carbonate, add them to 1 L of water, stir until evenly dispersed to obtain solution 3;

[0083] S2. Add solution 2 and solution 3 obtained in step S1 dropwise, and mix them in a colloid mill at a rotor speed of 3900 rpm for 4.8 min. After the mixture is finished, the mixture is allowed to stand at 88° C. for 2.5 h, and centrifuged at a centrifugal force of 3300 g for 16 min to obtain a precipitate. The precipitate is washed 5 times with deionized water, and a dopamine hydrochloride solution having a mass percentage concentration of 0.7% is added. The mass volume ratio of the precipitate: the dopamine hydrochloride solution is 1 g: 15 mL. The mixture is stirred at a speed of 320 rpm at room temperature for 2.9 h. After the mixture is finished, the mixture is centrifuged. The precipitate is dried to obtain a hardening accelerator.

[0084] This embodiment also provides a method for preparing the alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent, and the specific steps are as follows:

[0085] M1. Weigh the components according to mass percentage, dissolve the polyaluminum sulfate in 16 parts of water, then add the hardening accelerator and ethylene glycol ethyl ether, heat to 78 ° C and stir until uniformly dispersed to obtain a solution 4;

[0086] M2. Dissolve aluminum triformate, calcium formate and modified nano-silica in the remaining 42 parts of water and stir until uniformly dispersed to obtain a solution 5;

[0087] M3. The solution 4 obtained in step M1 is mixed with the solution 5 obtained in step M2, and the polymer thickener is slowly added, and stirred until it is evenly dispersed to obtain an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent.

[0088] Embodiment 5: This embodiment provides an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent, the components of which are as follows by mass: 50 parts of polyaluminium sulfate, 8 parts of aluminium triformate, 1.5 parts of ethylene glycol ethyl ether, 3 parts of polymer thickener, 3 parts of modified nano-silica, 5 parts of hardening accelerator, 2 parts of calcium formate and 60 parts of water;

[0089] The preparation method of the polymeric thickener is as follows:

[0090] V1. Acrylic acid and N,N-dimethylacrylamide were weighed in a molar ratio of 3:1 to obtain a mixture 1, and the mixture 1 and water were weighed in a volume ratio of 1:15, and the pH was adjusted to 7.0 with sodium hydroxide to obtain a mixture 2, nitrogen was introduced into the mixture 2 at a flow rate of 10 L / min, and a 3% ammonium persulfate solution with a mass percentage of 8% of the volume of the mixture 2 was dripped, and the mixture was heated to 70°C and stirred at a rotation speed of 120 rpm for 5 hours, and cooled to room temperature to obtain a mixture 3;

[0091] V2. The mixture 3 obtained in step V1 was centrifuged at 5000 g centrifugal force, the supernatant was discarded, the precipitate was washed 5 times with deionized water, and the precipitate was centrifuged again and dried to obtain a polymer thickener;

[0092] The preparation method of modified nano silicon dioxide is as follows:

[0093] L1. Stearic acid and anhydrous ethanol were mixed in a mass volume ratio of 1 g:7 mL, heated to 55°C, and stirred at 600 rpm until uniformly dispersed to obtain solution 1;

[0094] L2. The nano-silica particles were added to the solution 1 obtained in step L1, and then dispersed by ultrasonic treatment at 200w power, heated to 65°C and maintained for 3h, and then filtered, washed with anhydrous ethanol, and dried to obtain modified nano-silica;

[0095] The preparation method of the hardening accelerator is as follows:

[0096] S1. Weigh 1.5 mol of aluminum nitrate and 1.5 mol of lithium nitrate, add them to 1 L of water, stir until evenly dispersed to obtain solution 2, weigh 1.2 mol of sodium hydroxide and 1.0 mol of sodium carbonate, add them to 1 L of water, stir until evenly dispersed to obtain solution 3;

[0097] S2. Add solution 2 and solution 3 obtained in step S1 dropwise, and mix them in a colloid mill at a rotor speed of 4000 rpm for 5 minutes. After the mixture is finished, the mixture is allowed to stand at 90°C for 3 hours, and centrifuged at a centrifugal force of 3000 g for 15 minutes to obtain a precipitate. The precipitate is washed 5 times with deionized water, and a dopamine hydrochloride solution having a mass percentage concentration of 0.8% is added. The mass volume ratio of the precipitate: the dopamine hydrochloride solution is 1 g: 15 mL. The mixture is stirred at a speed of 320 rpm at room temperature for 3 hours. After the mixture is finished, the mixture is centrifuged, and the precipitate is dried to obtain a hardening accelerator.

[0098] This embodiment also provides a method for preparing the alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent, and the specific steps are as follows:

[0099] M1. Weigh the components according to mass percentage, dissolve the polyaluminum sulfate in 20 parts of water, then add the hardening accelerator and ethylene glycol ethyl ether, heat to 80 ° C and stir until uniformly dispersed to obtain a solution 4;

[0100] M2. Dissolve aluminum triformate, calcium formate and modified nano-silica in the remaining 40 parts of water and stir until uniformly dispersed to obtain a solution 5;

[0101] M3. The solution 4 obtained in step M1 is mixed with the solution 5 obtained in step M2, and the polymer thickener is slowly added, and stirred until it is evenly dispersed to obtain an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent.

[0102] Comparative Example 1: This comparative example provides an accelerating setting agent, the specific contents of which are as follows:

[0103] The quick-setting agent described in this comparative example is different from that in Example 2 in that the same mass fraction of unmodified nano-silicon dioxide particles is used instead of modified nano-silicon dioxide, and the other components and the preparation method of the quick-setting agent are consistent with those in Example 2, and finally the quick-setting agent of this comparative example is obtained.

[0104] Comparative Example 2: This comparative example provides an accelerating setting agent, the specific contents of which are as follows:

[0105] The quick-setting agent of this comparative example is different from that of Example 3 in that the same mass fraction of polyacrylamide is used to replace the polymer thickener, and the other components and the preparation method of the quick-setting agent are consistent with those of Example 3, and finally the quick-setting agent of this comparative example is obtained.

[0106] Comparative Example 3: This comparative example provides an accelerating setting agent, the specific contents of which are as follows:

[0107] The quick-setting agent described in this comparative example is different from that in Example 4 in that it does not contain a hardening accelerator, and the other components and the preparation method of the quick-setting agent are consistent with those in Example 4, and finally the quick-setting agent of this comparative example is obtained.

[0108] Comparative Example 4: This comparative example provides an accelerating setting agent, the specific contents of which are as follows:

[0109] The quick-setting agent described in this comparative example has the following components in parts by mass: 48 parts of aluminum sulfate, 7.8 parts of magnesium fluorosilicate, 11.1 parts of triethanolamine, 0.8 parts of polyacrylamide, 2 parts of citric acid and 40 parts of water.

[0110] Accelerator performance test:

[0111] The performance test of the accelerators obtained in Examples 1-5 and Comparative Examples 1-4 was carried out. The experimental methods were based on the relevant provisions of GB / T 35159-2017 "Accelerators for Shotcrete", GB / T 8077-2023 "Test Methods for Homogeneity of Concrete Admixtures", GB / T 176-2017 "Cement Chemical Analysis Methods", and QCR 807-2020 "Liquid Alkali-free Accelerators for Tunnel Shotcrete". The specific contents are as follows:

[0112] 1. Determination of setting time:

[0113] The room temperature is controlled at 20±2℃, 400g cement and water (minus the water in the accelerator) are poured into the mixing pot, stirred at low speed for 30s, then the accelerator is added, stirred at low speed for 5s, stirred at high speed for 15s, and the stirring is stopped. The mixture is immediately filled into a round mold, rammed, vibrated, and smoothed. The time from adding the accelerator to smoothing shall not exceed 50s, and the measurement shall be performed every 10s until the initial setting and final setting. The same sample shall be measured twice, and the average of the two results shall be taken. If the two measured values ​​differ by 30s, the test shall be invalidated. The cement used in the experiment is PO42.5 (this cement is also used in other performance test experiments), and its chemical composition is shown in Table 1:

[0114] Table 1 Chemical composition of PO42.5 cement used in the experiment

[0115]

[0116] 2. Determination of compressive strength:

[0117] Pour the required water (450g minus the water in the accelerator) and 900g of cement into the mixing pot in sequence. First adjust the mixer to low speed, stir the cement and water in the pot at low speed for 30s, then evenly add 1350g of ISO standard sand (purchased from Xiamen Aisiou Standard Sand Co., Ltd.) in the second 30s, and then adjust to high speed stirring for 30s and pause. The pause time is 90s. During the pause, scrape the mortar that is not fully mixed and attached to the inner wall, bottom of the mixing pot and stirring blades into the pot. Then continue to stir at high speed for 30s and then start adding the weighed accelerator. The manual adjustment procedure is to start at low speed for 5s, then high speed for 15s and then stop. Then quickly transfer the mortar to the mortar mold, and then use the vibration table to vibrate for 30s. After smoothing the surface and marking it, place it in a standard curing box with the mold. Demould after 24h, and determine the compressive strength of the age to be tested according to regulations.

[0118] 3. pH determination:

[0119] When testing the pH value of the accelerator, clean the electrode with distilled water in advance and absorb excess water, then turn on the instrument to preheat for 30 minutes, then measure the temperature of the accelerator to be tested and the calibration solution, adjust the pH counter display temperature to be consistent with the accelerator, and then put the electrode into the calibration solution with a pH of 6.86 and 4.0 in turn for calibration. After the calibration is completed, the pH value of the accelerator can be tested.

[0120] 4. Stability determination:

[0121] Place the accelerator into three 100mL measuring cylinders with stoppers. Accurately measure 100mL of liquid in each measuring cylinder. Then place the three measuring cylinders with stoppers in an environment with a temperature of 20±2℃, avoiding direct sunlight. After 28 days, read the volume V1 of the supernatant in the measuring cylinder or the volume V2 of the bottom sediment. The test result is expressed as the middle value of the three values ​​of V1 or V2.

[0122] 5. Determination of chloride ion, fluoride ion and alkali content:

[0123] The determination of chloride ion and alkali content is carried out in accordance with the relevant records of GB / T 8077-2023, wherein the chloride ion content is determined by ion chromatography, the alkali content is determined by atomic absorption spectrophotometry, and the fluoride ion content is determined by referring to the relevant records of GB / T 176-2017, specifically the ion selective electrode method.

[0124] The experimental results of the performance test of the quick-setting agent obtained in Examples 1-5 and Comparative Examples 1-4 are as follows:

[0125] Table 2 Performance test results of accelerator 1

[0126]

[0127] Table 3 Accelerator performance test results 2

[0128]

[0129] Experimental verification shows that the quick-setting agent obtained by the present invention has a better application effect when the addition amount is 4-10%. Tables 2 and 3 show the performance test results when the addition amount is 7%. Figure 1 This is a SEM picture of the accelerated setting agent obtained in Example 3 after being mixed with cement at an addition amount of 7%.

[0130] It can be seen from Table 2 and Table 3 that the accelerators obtained in Examples 1-5 have an initial setting time of ≤5 min, a final setting time of ≤12 min, a 1d compressive strength of ≥7.0 MPa, a 28d compressive strength ratio of ≥90%, a pH of ≥2.0, a stability of ≤5 mL, a chloride ion content of ≤0.1%, a fluoride ion content of all detected, and an alkali content of ≤1.0%, which meets the performance requirements of the alkali-free accelerator specified in the current standards, and the chloride ion and fluoride ion contents are also within the specified range. The present invention prepares an alkali-free, fluorine-free, and chlorine-free accelerator.

[0131] In addition, the quick-setting agents obtained in Examples 1-5 have excellent formulas, better overall use effects, shorter initial and final setting times, and higher strength and retention rates of concrete after use, proving that the quick-setting agents prepared by the present invention have excellent performance in all aspects and can be efficiently used in the construction industry.

[0132] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the protection scope of the technical solution of the present invention.

Claims

1. An alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent, characterized in that: The components of the accelerating setting agent are as follows by mass: 40-50 parts of polyaluminium sulfate, 3-8 parts of aluminium triformate, 1-1.5 parts of ethylene glycol ethyl ether, 2-3 parts of polymer thickener, 1-3 parts of modified nano-silicon dioxide, 3-5 parts of hardening accelerator, 1-2 parts of calcium formate and 50-60 parts of water; The preparation method of the polymeric thickener is as follows: V1. Acrylic acid and N,N-dimethylacrylamide are weighed in a molar ratio of 1-3:1 to obtain a mixture 1, and mixture 1 and water are weighed in a volume ratio of 1:10-15, and the pH is adjusted to 7.0 to obtain a mixture 2, nitrogen is introduced into the mixture 2, and an ammonium persulfate solution is added dropwise, and the mixture is heated and stirred continuously for 4-5 hours, and cooled to room temperature to obtain a mixture 3; V2. The mixture 3 obtained in step V1 is centrifuged, the supernatant is discarded, the precipitate is washed with deionized water, and the precipitate is centrifuged again and dried to obtain a polymer thickener; The preparation method of the modified nano silicon dioxide is as follows: L1. Stearic acid and anhydrous ethanol were mixed in a mass volume ratio of 1 g: 5-7 mL, heated and stirred until uniformly dispersed to obtain solution 1; L2. The nano-silica particles are added to the solution 1 obtained in step L1, dispersed by ultrasonic treatment and then heated to maintain, filtered, washed with anhydrous ethanol, and dried to obtain modified nano-silica; The preparation method of the hardening accelerator is as follows: S1. Aluminum nitrate and lithium nitrate were added to water and stirred until uniformly dispersed to obtain solution 2, sodium hydroxide and sodium carbonate were added to water and stirred until uniformly dispersed to obtain solution 3; S2. Add solution 2 and solution 3 obtained in step S1 dropwise and grind to mix, heat and let stand after completion, centrifuge to obtain precipitate 1, wash precipitate 1 with deionized water, add dopamine hydrochloride solution, stir at room temperature, centrifuge after completion, and dry precipitate 2 to obtain a hardening accelerator.

2. The alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent according to claim 1, characterized in that: Among the components of the accelerating setting agent, the mass portion of polyaluminium sulfate is 45-48 parts, and the mass portion of aluminium triformate is 4-6 parts.

3. The alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent according to claim 2, characterized in that: In step V1, the mass percentage concentration of the ammonium persulfate solution is 1-3%, and the amount of the ammonium persulfate solution added is 5-8% of the volume of the mixture 2.

4. The alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent according to claim 3, characterized in that: In step S1, the molar ratio of aluminum nitrate: lithium nitrate is 1:1, the concentration of aluminum nitrate in solution 2 is 1.2-1.5 mol / L, the molar ratio of sodium hydroxide: sodium carbonate is 1.2:1, and the concentration of sodium hydroxide in solution 3 is 0.9-1.2 mol / L.

5. The alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent according to claim 4, characterized in that: In step S2, the mass percentage concentration of the dopamine hydrochloride solution is 0.5-0.8%, and the mass volume ratio of precipitate 1: dopamine hydrochloride solution is 1 g: 10-15 mL.

6. A method for preparing the alkali-free, chlorine-free and fluorine-free high-efficiency quick-setting agent according to any one of claims 1 to 5, characterized in that: The specific preparation steps are as follows: M1. Weigh the components in parts by mass, dissolve the polyaluminum sulfate in 10-20 parts of water, then add the hardening accelerator and ethylene glycol ether, heat to 70-80 ° C and stir until uniformly dispersed to obtain a solution 4; M2. Dissolve aluminum triformate, calcium formate and modified nano-silica in the remaining mass parts of water and stir until uniformly dispersed to obtain a solution 5; M3. The solution 4 obtained in step M1 is mixed with the solution 5 obtained in step M2, and the polymer thickener is slowly added, and stirred until it is evenly dispersed to obtain an alkali-free, chlorine-free, and fluorine-free high-efficiency quick-setting agent.

Citation Information

Patent Citations

  • Temperature-resistant and pressure-resistant cement-based plugging material and preparation method thereof

    CN112624712A

  • Alkali-free fluorine-free liquid accelerator and preparation method thereof

    CN114276042A

  • Wet-mixed mortar admixture and preparation method thereof

    CN114685085A

  • Impermeable accelerator and preparation method thereof

    CN115784664A

  • Reinforcing agent for curing-free pervious concrete as well as preparation method and application of reinforcing agent

    CN117510124A

Cited By

  • Low-rebound early-strength type alkali-free liquid accelerator and preparation method thereof

    CN122853745A